Exergy analysis and performance evaluation of flow and heat transfer in different micro heat sinks with complex structure. (May 2015) - Zhai, Y.L.; Xia, G.D.; Liu, X.F.; Li, Y.F.
Abstract: Simulations are conducted to investigate flow and heat transfer performance of de-ionized water flowing through different micro heat sinks with complex structure under uniform heat flux. Six new micro heat sinks with different types of cavities and ribs are proposed. Moreover, they are compared involving friction factor and Nusselt number relative to other micro heat sinks in the existed literature. Exergy analysis is also applied to investigate the physical mechanism of heat transfer enhancement. Different performance evaluation criteria, based on first and second law of thermodynamics, are proposed to assess the overall performance of micro heat sinks. The results clearly show that the micro heat sink with triangular cavities and triangular ribs (Tri.C–Tri.R for short) presents the best heat transfer performance over a Reynolds number range of 300–600. The performance of heat transfer can be enhanced by decreasing the net temperature gradient of fluid in micro heat sinks. New correlations of friction factor and Nusselt number are proposed based on numerical data, which relate with Reynolds number and relative cavity height and relative ribs height.